Clinico-Radiographic Discordance: An Evidence-Based Commentary on the Management of Degenerative Cervical Spinal Cord Compression in the Absence of Symptoms or With Only Mild Symptoms of Myelopathy. Issue 5 (August 2018) - Witiw, Christopher D.; Mathieu, Francois; Nouri, Aria; Fehlings, Michael G.
Study Design: Narrative review with commentary. Objectives: The growing use of magnetic resonance imaging (MRI) often leaves clinicians faced with scenarios where imaging findings are inconsistent with the clinical picture. This is particularly relevant for degenerative cervical spinal cord compression (CSCC). In this article, we provide a focused narrative literature review to address whether (1) surgery should be offered to asymptomatic patients with CSCC and (2) should MRI spinal cord signal changes influence clinical decisions for a patient with mild myelopathy from CSCC? Methods: Illustrative cases are presented with expert commentary which is supplemented by a focused literature review. Results: The literature suggests that CSCC from degenerative pathology is a common incidental radiographic finding. For those without symptoms of myelopathy, the short-term risk of progression is low. There is a lack of evidence to support surgery for asymptomatic individuals with CSCC who have no risk factors for progression. For these patients, the authors suggest non-operative management that includes education on the symptoms of myelopathy, clinical follow-up within 6 to 12 months, and avoidance of high-risk activities. Conversely, symptomatic patients have a notable risk of progression. Surgical intervention improves neurological function and quality of life regardless of severity. The authors support surgery as an option for all patients with mild myelopathy who are appropriate operative candidates. Intramedullary signal change on MRI has not been shown to reliably predict progression. Conclusions: While MRI technologies are under evolution, we advise that surgical decisions for patients with CSCC should rely on clinical assessment and not imaging findings.